Image of a left atrial mass after a cardiopulmonary bypass in a child. Issue 10 (30th May 2017) - Hadeed, Khaled; Leobon, Bertrand; Dulac, Yves; Acar, Philippe
Abstract : Invagination of an appendage into the left atrium is a rare complication. It occurs spontaneously or after open‐heart surgery. In our case, a postoperative transesophageal echocardiogram, after closure of a ventricular septal defect in a 5‐month‐old infant, revealed a large mass in the left atrium. A diagnosis of a left appendage inversion was confirmed after external examination of the heart. Herein, we provide echocardiographic images before, during, and after manual reversion of the left appendage. Misdiagnosis of this complication could have led to an additional unnecessary surgical procedure that could have impacted on the patient's morbidity.